Implementing Synchronize Service From Open Journal System into Laravel Journal House Information System - Huygenz Widodo, Raden Ibnu; Nengsih, Titin Agustin (CV. Generasi Intelektual Digital, 2025)
The increasing complexity of managing academic journals has highlighted the need for efficient systems that ensure seamless data synchronization across platforms. Existing solutions often involve fragmented workflows, resulting in redundant manual tasks and data inconsistencies. This study proposes an integration of the Open Journal System (OJS) with a Laravel-based Journal House Information System through a custom API synchronization service. The method employs Express.js and MySQL to facilitate real-time, automated data transfer, streamlining journal management and improving accuracy. Developed using the Agile methodology, the system was rigorously tested for performance and functionality, demonstrating its ability to efficiently handle large datasets. The proposed solution reduces administrative workload, enhances data consistency, and provides a scalable model for academic institutions seeking to improve their journal management workflows